New detection method of SARS-CoV-2 antibodies toward a point-of-care biosensor - Nelson-Mora, Janikua; Rubio, Diana; Ventura-Martínez, Amairani; González, Luis A.; Del-Rio, Diana; Aranda-López, Yuli; Jiménez-Díaz, Edgar; Zamarrón-Hernández, Diego; Ríos-López, Diana G.; Aguirre, Stephanie; Ruiz-Hernandez, Yasab; Cruz-Ramírez, Aarón; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
The outbreak of COVID-19, a disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, is regarded as the most severe of the documented coronavirus pandemics. The measurement and monitoring of SARS-CoV-2 antibodies levels by serological tests is relevant for a better epidemiological and clinical understanding of COVID-19. The aim of this work was to design a method called SARS-CoV-2 antibody detection method (SARS-CoV-2 AbDM) for fluorescence immunodetection of anti-SARS-CoV-2 IgG and IgM on both plate and microfluidic chip. For this purpose, a system with magnetic beads that immobilize the antigen (S protein and RBD) on its surface was used to determine in a single reaction the presence and quantity of antibodies in a sample. The SARS-CoV-2 AbDM led to a number of advantages in the performance of the tests such as reduced cost, the possibility of performing isolated or multiple samples, the potential of multiplex detection and the capacity to detect whole blood samples without losing resolution. In addition, with the microfluidic chip in conjunction with the motorized actuated platform, the time, sample quantity and operator intervention during the process were reduced. All these advantages suggest that the SARS-CoV-2 AbDM has the potential to be developed as a PoC that can be used as a tool for seroprevalence monitoring, allowing a better understanding of the epidemiological and clinical characteristics of PAGE \* ARABIC 12This is a provisional file, not the final typeset article COVID-19, and contributing to more effective and ethical decision-making in strategies to fight against the COVID-19 pandemic.